An exploratory study of relationships between stakeholders' risk perceptions and their roles and experience in construction industry. Issue 7 (3rd July 2021) - Al Nahyan, Moza Tahnoon; Hawas, Yaser E.; Raza, Mohsin
Abstract: This study explores relationship between variations in risk perceptions of various stakeholders and their roles and experience in the construction industry. A sample of 133 respondents from different stakeholder groups was picked from the UAE construction industry, and surveyed through an online questionnaire to collect data on respondents' experience, roles, and risk perceptions. Variations in risk perceptions were analyzed by grouping the respondents by experience and roles. Given the ordinal nature of the data, only nonparametric statistical techniques were used in the analysis. According to the results, the roles and experience of stakeholders significantly affected their risk perceptions in many cases. For example, there was a statistically significant discordance between clients and contractors regarding the importance of delegating decision-making authority. Likewise, significant discordance was observed between more experienced and less experienced sub-groups of clients regarding the importance of design quality and documentation.